THE DEVELOPMENT OF JUDAISM IN THE SIXTH MILLENNIUM - Maller, Rabbi Allen S (Journal of Dharma, 2001)
Judaism is not a religion of eternal universal ttmth. Judaism is based on the meaning given to specific events in Jewish history, especially the covenant (a holy committed relationship) between God and the Jewish People which commits them to establish a good and holy society, that would eventually become a blessing for all humanity in a future Messianic Age on earth. Thus, the meanings of specific events in Jewish history are important elements in Jewish thought. Since there is only one God, the God of Israel is also the God of all other peoples. God has inspired prophets of other nations (Noah, Melchizedik, and Balaam) and redeemed other peoples in Other lands (Deuteronomy 2;9-23, Amos 9:7). God has also made a covenant - a committed sacred relationship - with one small people: the people of Israel. God and Israel are partners. Thus, the historical development of the Jewish people, its survival in spite of attempts by evil forces to destroy it, and its influence on the development of mankind, are a significantexpression of God’s desire that humans create a just, holy, loving and peaceful society on earth. This is why Jewish sacred scriptures include a great deal of history. Of the 39 books in what Christians call the Old Testament, 10 are history books (36% by number of pages). Of the 27 books of the New Testament only 1 is a history book (13% by number of pages). The Koran, Vedas and Sutras include even less historical material.